Trabajo colaborativo entre docentes - Jaramillo Carrillo, Erika Hidai (2016)
The purpose of this research is to introduce teachers to the importance of collaboration among co-workers to achieve the unification of teachers with the problems that exist in education at the present time, hence this research project it is based on the following objective: "to analyze the collaborative research among teachers, through their educational components, to facilitate curricular activities in school teachers at “Loja Basic General Education". This research is an answer to the problem wich: consists in .How will the lack of collaborative research in teachers influences within the development of curricular activities? For the development of this research methodological processes were discussed, sachas the descriptive method, because it allowed detailing situations on collaborative research in education, types and ways to educate, the inter-learning, methodological strategies, what a educational institution ,is the role of teachers, education research and as a group, also researchers took into account the motivation as an essential part of the beginning of the teaching research, collaboration and basic conditions they , pointed out the difficulties of collaborative work, advantages of research ,as well as the main values within the educational field. Researchers worked with the population universe, being somewhat reduced, then they asked the following scientific questions consisting of: -What is the nature of collaborative work in education, to have a clear conceptualization of this activity? -How important is the collaborative work in education, to know the advantages of their application? -How influences the fundamental values influence that have to do with the collaborative research, to use in the educational field? Then researchers into consideration the conclusions and recommendations reached in this research work.